Endovascular aortic repair: single centre experience of thoracic endovascular aortic repair and endovascular aneurysm repair - Faizan Nihal; Talha Kareem; Omer Ehsan; Ahmed, Muhammad Adeel; Nazish Ali; Zahid Amin (Journal of the Pakistan Medical Association, 2025)
This retrospective case series evaluates the experience of endovascular aortic repair procedures at a single centre in Pakistan, focussing on patient selection, procedural feasibility, and associated challenges. The study includes 21 patients (six women and 15 men) who underwent various endovascular interventions: six received endovascular aneurysm repair (EVAR), one underwent fenestrated EVAR (FEVAR), 12 had thoracic endovascular aortic repair (TEVAR), and two underwent interventions for aortic coarctation. Of these procedures, seven were performed in emergency settings, while fourteen were elective. The results highlight the effectiveness of endovascular techniques in reducing operative mortality and morbidity for aortic aneurysms and dissections. However, limited accessibility in Pakistan due to high costs and scarcity of specialised referral centres restricts widespread implementation. Strengthening vascular services, improving affordability, and increasing awareness among healthcare professionals and patients could enhance the adoption of these life-saving procedures. Keywords: EVAR, TEVAR, Endovascular repair, Abdominal aortic aneurysm, FEVAR, Vascular interventions, Aortic coarctation.